APLIKASI METODE BIOAUTOGRAFI DALAM PENELUSURAN DAYA ANTIBAKTERI EKSTRAK PEGAGAN (Centella asiatica (L.)) - Rehmadanta Sitepu; Ririn Nurdiani; Rollando Rollando (LLDIKTI Wilayah X, 2020)
Pegagan (Centella asiatica (L.) Urban) is a traditional herbal plant that spread as it grows and in bloom througout the year. Pegagan is believed to be able to cure various type of diseases because it contains bioactive component that’s good for human body. Pegagan’s bioactive component that has anti-bacterial properties are saponin, flavonoid, and tanin. This study was conducted with the purpose to determine the existence of antibacterial activity in ethanol extract of pegagan leaves by applying it in Disc Diffusion Test method against Escherichia coli and Staphylococcus aureus bacteria. Etanol extract was obtained by using maserasi method with 70% ethanol, separation of the active compound group which one of them is flavonoid using phytochemical screening, and the result was that the pegagan positively contains flavonoid, it was proven by the existence of a red marker on the tube. The result of active compund using methanol eluent: chloroform: glacial acetic acid produces 1 spot point on (Rf 0,5-0,7) on TLC. This spot was used in antibacterial screening by bioatugraphy method and the activity was detected qualitatively. Antibacterial activity was proved by Disc Diffusion Test which the results were ethanol extract on pegagan has inhibitory activity to E.coli and S. aureus. This study can be concluded that ethanol extract of Centella asiatica has a MIC value of 3,200 µg / mL both in E. Coli and S. aureus. The diameter of obstacles zone were 0,06±0,05 mm to E.coli and 0,04±0,019 mm to S. aureus.Centella asiatica (L.) Urban (Pegagan) adalah spesies tumbuhan herbal tradisional dengan karakteristik tumbuh merambat dan berbunga di sepanjang tahun. Komponen bioaktif yang dimiliki pegagan dalam beberapa aspek, dapat digunakan dalam pengobatan penyakit. Golongan-golongan senyawa bioaktif pegagan yang memiliki daya antibakteri adalah saponin, flavonoid, dan tanin. Penelitian ini bertujuan untuk mengetahui adanya aktivitas antibakteri ekstrak etanol daun pegagan dengan metode Disc Diffusion Test pada Escherichia coli maupun Staphylococcus aureus. Ekstrak tanaman Pegagan diperoleh dengan maserasi dengan etanol 70%, pemisahan golongan senyawa aktif salah satunya flavonoid menggunakan skrining fitokimia, yang secara kualitatif menunjukkan ekstrak tanaman mengandung flavonoid. Hasil Kromatografi Lapis Tipis (KLT) senyawa aktif menggunakan eluen metanol: kloroform: asam asetat glasial menghasilkan 1 titik spot pada Rf 0,5-0,7 digunakan dalam penelusuran pengujian daya antibakteri dengan metode autobiografi dan menunjukkan adanya pembentukan zona bening. Pada uji kuantitatif, ekstrak etanol pegagan memiliki nilai KHM 3.200 µg/mL baik pada Eschericia coli maupun Staphylococcus aureus. Nilai Kadar Bunuh Minimum (KBM) lebih dari 6.400 µg/mL aktivitas daya hambat dengan diameter 0,06±0,05 mm pada E.coli dan 0,04±0,019 mm untuk S. aureus.